Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/1440-1681.12848
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin ameliorates severe influenza pneumonia via attenuating lung injury and regulating macrophage cytokines production

Abstract: SummaryCurcumin, an active phenolic agent extract from the Curcuma longa, exhibits excellent anti-cancer, anti-inflammation, and neuroprotective effects. We aimed to investigate cytokines. In addition, curcumin was found to inhibit NF-κB signalling in macrophages, as well as the subsequent production of cytokines/chemokines responding to IAV infection, by enhancing IκBα and AMPK. Our current study supports the potential of curcumin as a promising treatment against IAV infection, whose effect may be mediated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 40 publications
2
91
0
1
Order By: Relevance
“…Importantly, curcumin treatment by oral gavage (50 and 150 mg/kg) reduced IAV replication and lung injury in an in vivo animal model [19], clearly illustrating that curcumin can provide a therapeutic benefit to combat infection and virus-induced disease. This latter observation was supported by a study by Han et al [53], who demonstrated that mice infected with the IAV strain PR8 and fed 30 or 100 mg/kg of curcumin had increased survival, reduced bodyweight loss, and lower IAV burden in lung tissues as determined by immunohistochemistry. Bronchoalveolar lavage (BAL) fluid and lung tissues from infected, curcumin-treated mice had lower levels of monocyte chemoattractant protein-1 (MCP-1) and tumour necrosis factor-alpha (TNFα) compared to untreated mice, suggesting reduced inflammation.…”
Section: Influenza a Virusmentioning
confidence: 57%
“…Importantly, curcumin treatment by oral gavage (50 and 150 mg/kg) reduced IAV replication and lung injury in an in vivo animal model [19], clearly illustrating that curcumin can provide a therapeutic benefit to combat infection and virus-induced disease. This latter observation was supported by a study by Han et al [53], who demonstrated that mice infected with the IAV strain PR8 and fed 30 or 100 mg/kg of curcumin had increased survival, reduced bodyweight loss, and lower IAV burden in lung tissues as determined by immunohistochemistry. Bronchoalveolar lavage (BAL) fluid and lung tissues from infected, curcumin-treated mice had lower levels of monocyte chemoattractant protein-1 (MCP-1) and tumour necrosis factor-alpha (TNFα) compared to untreated mice, suggesting reduced inflammation.…”
Section: Influenza a Virusmentioning
confidence: 57%
“…Although a review of AMPK-modulating polyphenols is beyond our scope, we highlight the therapeutic promise of polyphenols against infection. For example, curcumin from Curcuma longa inhibits influenza A viral infection in vitro and in vivo, at least in part by activating AMPK [ 36 ]. The polyphenol epigallocatechin gallate attenuates Tat-induced human immunodeficiency virus (HIV)-1 transactivation by activating AMPK [ 37 ].…”
Section: Multifaceted Role Of Ampk In Antimicrobial Responsesmentioning
confidence: 99%
“…It has, therefore, been associated with more than 100 cellular targets, including cytokine s, proteins, transcription factors, and receptors. Previous studies have shown the potential of curcumin as a treatment against Influenza A virus infection, by an effect mediated by modulating immune response to prevent injury to the lung tissue (Han, Xu, Guo & Huang 2018). Curcumin has also been shown to have anti neuraminidase (NA) activity for the influenza virus NA protein (Richart et al 2018).…”
Section: Introductionmentioning
confidence: 99%